Causes of Maternal Death During Childbirth in Tehran-Iran in 2011-2015 - Farzianpour, Fereshteh; Emami, Amir Hossein; Ramezani, Khatere (Pakistan Journal of Nutrition, 2017)
Background and Objective: The occurrence of maternal death would threaten the family foundation and children’s health. The aim of this study was to determine the causes of maternal deaths during childbirth in Tehran province, Iran in 2011-2015. Materials and Methods: All Maternal Mortality Ratio (MMR) in Tehran province from 2011-2015 were considered in this cross-sectional study. Data were recorded for demographic characteristics, autopsy findings, medical and obstetric histories. The data were then analyzed with a z-test to identify differences in the rate of MMR during the study period. Results: The mean MMR was 15.8 in 100,000 live births (95% CI, 1.076-13.546) during the 5 years study period and the highest MMR was 19.1 in 2011 and the lowest proportion was 13 in 2015. Most deaths (23.6%) occurred in the preeclampsia-eclampsia period and the lowest autoimmune disease and addiction (1.8%). High-risk mothers accounted for 79.2% of maternal deaths. Among the mothers who died, 50.45% received satisfactory prenatal care and at least 2 years elapsed between successive pregnancies in 23.8%. Vaginal bleeding was the main cause of death (33.8%). Conclusion: The MMR has been declining over the years, due to the identified factors associated with maternal death, proposed strategies, such as improving the quality of hospital services.